Modulation of mechanical properties of short bioinspired peptide materials by single amino-acid mutations - Hiew, Shu Hui (2023)
The occurrence of modular peptide repeats in load-bearing (structural) proteins is common in nature, with distinctive peptide sequences that often remain conserved across different phylogenetic lineages. These highly conserved peptide sequences endow specific mechanical properties to the material, such as toughness or elasticity. Here, using bioinformatic tools and phylogenetic analysis, we have identified the GX8 peptide with the sequence GLYGGYGX (where X can be any residue) in a wide range of organisms. By simple mutation of the X residue, we demonstrate that GX8 can be self-assembled into various supramolecular structures, exhibiting vastly different physicochemical and viscoelastic properties, from liquid-like coacervate microdroplets to hydrogels to stiff solid materials. A combination of spectroscopic, electron microscopy, mechanical, and molecular dynamics studies is employed to obtain insights into molecular scale interactions driving self-assembly of GX8 peptides, underscoring that π-π stacking and hydrophobic interactions are the drivers of peptide self-assembly, whereas the X residue determines the extent of hydrogen bonding that regulates the macroscopic mechanical response. This study highlights the ability of single amino-acid polymorphism to tune the supramolecular assembly and bulk material properties of GX8 peptides, enabling us to cover a broad range of potential biomedical applications such as hydrogels for tissue engineering or coacervates for drug delivery.